2016
DOI: 10.1016/j.agee.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon sequestration rates under Mediterranean woody crops using recommended management practices: A meta-analysis

Abstract: Revision Notes "Eq. 4. I recommend to replace k with j. K could result in misunderstanding (it could be mixed up with a rate constant)" We totally agree with this comment of the reviewer. Therefore, it has been changed. L. 371-372 of the new version. Please present in a new table the mean temperature and rainfall for each sub-climate regions used in the study. We acknowledge the comment of the reviewer. We decided to not to include a table with values of temperature and precipitations due to the high complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 61 publications
9
93
2
1
Order By: Relevance
“…5). The same C sequestration rates were found in Mediterranean environments after the conversion from conventional to alternative soil management using cover cropping residues: for instance, in a meta-analysis (16 studies) Vicente-Vicente et al (2016) found average values of C sequestration of 0.78 Mg ha -1 y -1 after the conversion of orchard from conventional to cover crop soil management. In a meta-analysis (74 studies), Gattinger et al (2012) found, on average, a C gain of 0.45 ± 0.21 Mg C ha −1 y −1 for organic treatments in comparison to conventional management.…”
Section: Soil Organic Carbon Stock and Sequestration Ratementioning
confidence: 53%
“…5). The same C sequestration rates were found in Mediterranean environments after the conversion from conventional to alternative soil management using cover cropping residues: for instance, in a meta-analysis (16 studies) Vicente-Vicente et al (2016) found average values of C sequestration of 0.78 Mg ha -1 y -1 after the conversion of orchard from conventional to cover crop soil management. In a meta-analysis (74 studies), Gattinger et al (2012) found, on average, a C gain of 0.45 ± 0.21 Mg C ha −1 y −1 for organic treatments in comparison to conventional management.…”
Section: Soil Organic Carbon Stock and Sequestration Ratementioning
confidence: 53%
“…Data are represented by box and whisker plots (central point means, and 95% confidence interval CI) following the method reported in previous data-analyses [25,81]. Responses were considered significantly different if their 95% CIs did not overlap, and significantly different from the controls if the 95% CIs did not overlap with zero [19,20,82]. Furthermore, correlation statistics for SOC content changes were performed based on a non-parametric Spearman rank analysis [22,25] including 26, 22, and 23 qualitative and quantitative predictors derived from the data-set for tillage management, crop diversification, and fertilization management respectively (Table S1).…”
Section: Data Evaluationmentioning
confidence: 99%
“…Similarly, green manuring increases the biomass returned to the soil, which results in the form of enlarged soil carbon sink. Studies reveal that the adoption of cover crops is an efficient measure to mitigate climate change [82]. According to Olson 2010 [83], the use of cover crops in intensive row crop rotations with different tillage treatments has been found to sequester soil organic carbon (SOC).…”
Section: Cover Cropsmentioning
confidence: 99%